2013
DOI: 10.1155/2013/740351
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Plasma and Urine Neutrophil Gelatinase Associated Lipocalin (NGAL) and Cystatin C in Early Diagnosis of Septic Acute Kidney Injury in Critically Ill Patients

Abstract: Abstract. AIM:To assess and compare the roles of plasma and urine concentrations of neutrophil gelatinase associated lipocalin (NGAL) and Cystatin C for early diagnosis of septic acute kidney injury (AKI) in adult critically ill patients. METHODS: Patients were divided into three groups as sepsis-non AKI, sepsis-AKI and non sepsis-non AKI. Plasma samples for NGAL and Cystatin C were determined on admission and on alternate days and urinary samples were collected for every day until ICU discharge. RESULTS: One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 28 publications
(53 reference statements)
1
52
0
2
Order By: Relevance
“…We have demonstrated a strong correlation between markers of inflammatory status (WBC, CRP, PCT) and both sNGAL and uNGAL. The fact that the correlation between NGAL levels and CRP or PCT was stronger than with WBC values, indicates damage to endothelial cells other than of tubular origin 6,7,22,23,25 plays a greater role in the release of NGAL than the activation of neutrophils. It is well known that immunological response of immature newborns is weaker and neutrophil activation limited.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have demonstrated a strong correlation between markers of inflammatory status (WBC, CRP, PCT) and both sNGAL and uNGAL. The fact that the correlation between NGAL levels and CRP or PCT was stronger than with WBC values, indicates damage to endothelial cells other than of tubular origin 6,7,22,23,25 plays a greater role in the release of NGAL than the activation of neutrophils. It is well known that immunological response of immature newborns is weaker and neutrophil activation limited.…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18][19][20][21] A new potential biomarker postulated as a more sensitive parameter of AKI is NGAL. 22 The introduction of this parameter into routine diagnostic workup requires establishing the reference values and knowledge of methodological limitations. Our study gives rise to the need of determining normal ranges of age and BW, especially of uNGAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadar NGAL urin pada 2 jam menjalani CPB hampir secara sempurna memprediksi pasien yang akan berkembang menjadi CGA. 7 Penelitian lain pada 103 orang dewasa yang menjalani cardiopulmonary bypass (CPB), ternyata CGA berkembang 31% pada mereka yang kadar KIM-1 urinnya meningkat sekitar 40% setelah 2 jam operasi dan 100% pada waktu jam ke-24. 8 Dengan demikian, KIM-1 merupakan kandidat yang menjanjikan untuk dimasukkan dalam penanda biologis CGA urin.…”
Section: Pendahuluanunclassified
“…uNGAL was also measured in one study of sepsis in which 63 (42%) patients out of 151 patients had increased uNGAL. 23 Haase-Fielitz et al 24 studied adult cardiac surgery patients and they reported that predictive value of plasma NGAL increases with increasing grade of AKI.…”
mentioning
confidence: 99%